Optimize investment portfolios Using statistical methods and Fuzzy approach (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of this research is the optimal portfolio selection using the Fuzzy Analytic HierarchyProcess (FAHP). This research is applied in terms of objective and descriptive-analytical interms of data collection and processing. The assessment models of strategic programs such asthe FAHP are utilized to conduct this research. The studied population consists of allcompanies listed on Tehran Stock Exchange during 2014-2019 and 7 companies areconsidered as the samples. The descriptive statistics including the demographic data ofstatistical sample such as the tables of frequency distribution, descriptive diagram, etc, areutilized for data analysis in this research and also the inferential statistics by FAHP is usedfor weighting the options. According to the results, the prioritization of portfolio selectioncriteria is as follows: Expected return, liquidity and risk criterion. Furthermore, theprioritization of studied listed companies is as follows: Esfahan's Mobarakeh Steel Company,Pipe and Machine Manufacturing Company of Iran, Borujerd textile Company, Rolling Mill& Steel Production Co., IRAN Merinos Co, Sadid Industrial Group, and Tous Wool WeavingCo.